Pemenuhan Hak Warga Negara Eks Timor Timur untuk Mendapatkan Kehidupan yang Layak - Irfan Fachrudin (Jurnal HAM, 2022)
East Timor is one of the provinces in Indonesia which separated itself as a result of the referendum in 1999 and became a country named Republik Deokratik Timor Leste (RDTL). As a result of the referendum, residents who wished to remain Indonesian citizens had to leave and then flee to the nearest area, one of which was in the Belu district, East Nusa Tenggara which is directly adjacent to East Timor. This research finds data that there are unfulfilled rights of citizens and solutions so that their rights can be fulfilled. The purpose of the research is to find out what rights have been received and aims to provide solutions so that their rights can be fulfilled. Collecting data by interviewing sources and then analyzing it. There are rights of ex-East Timorese that not been fulfilled, namely the right to have a proper place to live, the right to get a job, the right for children. The government must pay more attention to the conditions of the residents so that their rights are fulfilled. These problems can be handled by providing training and opening up job opportunities so that they can be independent and no longer live in refugee camps.